2012
DOI: 10.1021/jp307456m
|View full text |Cite
|
Sign up to set email alerts
|

25Mg Solid-State NMR of Magnesium Phosphates: High Magnetic Field Experiments and Density Functional Theory Calculations

Abstract: Natural-abundance 25 Mg solid-state NMR data obtained using very high magnetic fields of 17.6, 20.0, and 30.0 T are reported for a series of magnesium phosphate compounds, some of which are of potential biomedical interest. The 25 Mg NMR parameters have been calculated by using the DFT PAW and GIPAW methods, for both the experimental and DFT atomic position optimized structures. For most of the studied compounds, the geometry optimization step improves significantly the accuracy of the calculations and good co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
37
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 90 publications
8
37
0
Order By: Relevance
“…The GBFS/MKPC binder showed a similar 25 Mg MAS NMR spectrum to pure synthetic struvite-K, MgKPO 4 ·6H 2 O [56], in which Mg was found to be octahedrally coordinated within the crystal structure, represented by a single resonance with δ iso = −1.0 ppm, as Mg(OH 2 ) 6 . The quadrupolar parameters determined for struvite-K are comparable to those reported for struvite in the literature [57].…”
Section: Nuclear Magnetic Resonance Spectroscopysupporting
confidence: 84%
“…The GBFS/MKPC binder showed a similar 25 Mg MAS NMR spectrum to pure synthetic struvite-K, MgKPO 4 ·6H 2 O [56], in which Mg was found to be octahedrally coordinated within the crystal structure, represented by a single resonance with δ iso = −1.0 ppm, as Mg(OH 2 ) 6 . The quadrupolar parameters determined for struvite-K are comparable to those reported for struvite in the literature [57].…”
Section: Nuclear Magnetic Resonance Spectroscopysupporting
confidence: 84%
“…The spectra obtained from site D (5 to Á5 ppm) are more similar to those for inorganic forms of P including struvite (Cade-Menun 2005;Conte et al 2008;He et al 2009). The spectra obtained for sample 6 at site D are most similar to the spectra of struvite reported by Laurencin et al (2012). Sample preparation using water can dissolve phosphate species, such as struvite, which has a Ksp value of around 10 Á13 (von Vandruozka 2006).…”
Section: X-ray Diffraction Analysissupporting
confidence: 65%
“…The incorporation of the doping element in one or the other phases will deeply modify its potential release in biological fluid. The HAp structure is known to accept various ionic substitutions, as has been demonstrated for carbonate [16,17], silicate [18][19][20][21], borate [22,23] and alkaline earth cations Mg 2+ [24][25][26] and Sr 2+ [27,28]. Nevertheless our recent results on the Zn-doping mechanism demonstrated that substitution is not the only mechanism to be considered: insertion into an interstitial site [13], as also described for bevolite (the Sr equivalent with composition Sr 10 (PO 4 ) 6 (OH) 2 ) [29], has been established.…”
Section: -Introductionmentioning
confidence: 97%